Transumbilical laparoendoscopic single-site surgery for pregnancy complicated with ruptured giant ovarian teratoma in the third trimester: case report - Gong, Mei-Qin; Zhang, Yong-Qing; Hu, Ya-Yi; Wang, Xiao-Dong (Frontiers in Medicine, 2025)
BackgroundMost adnexal masses are incidental findings during pregnancy and usually resolve spontaneously. However, pregnancy complicated by a giant ovarian mass is rare, and surgical intervention is recommended when the mass exceeds 10 cm in diameter or persists during the pregnancy. Traditional laparoendoscopic surgery often requires extended periods of pneumoperitoneum, and the need for an initial blind puncture increases the risk of damaging the pregnant uterus and ovarian mass. With advancements in transumbilical laparoendoscopic single-site surgery, operating through an umbilical incision minimizes the potential harm associated with traditional laparoscopy, enhancing the safety of both the mother and fetus. Most literature reports operations conducted during the second trimester when the size and position of the uterus and placenta are optimal, ensuring stable placental function and a low risk of complications such as abortion or preterm birth. As the pregnancy progresses into the third trimester, the uterus moves approximately three transverse fingers above the umbilicus, making it extremely difficult to access a ruptured ovarian mass located posterior to the uterus using single-port laparoscopy. Nevertheless, with continuous improvements in transumbilical laparoendoscopic single-site surgery techniques, as well as the combination of long and short surgical instruments, it is feasible to address the rupture of a giant ovarian mass during the third trimester. Few reports currently detail the use of transumbilical laparoendoscopic single-site surgery for adnexal masses in the third trimester. This report presents a case completed at our hospital.Case presentationWe report the case of a giant ovarian tumor identified by ultrasound in the first trimester of pregnancy in a 27-year-old woman. Due to signs of threatened abortion, conservative treatment was chosen to allow the pregnancy to continue. The giant ovarian mass ruptured at 28+2 weeks of gestation, and it was successfully managed using transumbilical laparoendoscopic single-site surgery. The patient achieved a successful pregnancy, delivering at 38+5 weeks via emergency cesarean section due to oligohydramnios. We followed up with the mother and newborn for nearly 12 months, and they were healthy.ConclusionRoutine abdominal or vaginal ultrasound examinations before pregnancy are essential when a giant ovarian mass is detected in the first trimester. This helps prevent complications such as mass rupture, torsion, and adverse fetal outcomes. If surgical intervention is deemed necessary, the second trimester is generally the most appropriate time for evaluation. By this stage, the size and position of the uterus and placenta are stable, the placental function is sound, uterine sensitivity is lower, and the risk of miscarriage, premature birth, and other complications is reduced. For pregnant women with giant ovarian masses who exhibit signs of abortion in the second trimester and do not opt for surgical treatment, transumbilical laparoendoscopic single-site surgery can be considered the preferred method for addressing a mass rupture in the third trimester.